Productive in disagreement: stakeholder deliberation insights on carbon dioxide removal in Germany - Apergi, Maria; Hellmich, Mary; Eberenz, Samuel; Honegger, Matthias; Reinecke, Sabine; Tänzler, Dennis (Frontiers in Climate, 2024)
Attention to carbon dioxide removal (CDR) in climate policy is growing, and many CDR methods such as direct air carbon capture and storage (DACCS) are controversial. As such, broadening knowledge creation to include stakeholder perspectives upstream of policy is important. This exploratory study provides insights into the stakeholder engagement process of a transdisciplinary research project and its findings regarding co-creative CDR policy design and evaluation. It analyzes the views of participants in a stakeholder engagement workshop on CDR and an online survey. In all instances, experts highlighted the importance of the context in which these technologies are deployed. Workshop participants’ views of DACCS, including its risks and opportunities, evolved throughout the process, indicating that learning took place. We also present stakeholders’ reflections on their own role in knowledge creation and policy design. The qualitative experience and joint exploration of topics reaffirm the relevance of proper engagement on controversial, wicked problems such as the scaling of CDR as exemplified for DACCS. A nuanced discussion of the deployment context matters for stakeholders’ perception of DACCS. Our results underscore the importance of deliberative and adaptable policymaking in the current formative phase of CDR policy in Europe. Additionally, they highlight the need for policies to proactively address tradeoffs between climate mitigation efficiency and other goals. They advocate for government-backed CDR research and development (R&D) as a basis for future deployment alongside a fossil fuel phaseout to maintain a clear carbon budget and avert mitigation deterrence.